Determinan Minat Kunjung Kembali Wisata Halal Dengan Satisfaction Sebagai Variabel Intervening (Studi Kasus : Wisata Danau Lut Tawar Aceh Tengah) - Lathifah Aini (Journal of Economics, Bussiness and Management Issues, 2024)
The purpose of this research is focussed on Lake Lut Tawar tourist destinations in Central Aceh regency, especially in evaluating factors that have the potential to affect the desire of tourists to return to destination Lake Lut Tawar after experiencing a decrease in visit during the Covid-19 pandemic in 2020-2022.   This research is categorized as quantitative research because it adopts the paradigm of positivism, which tests a particular population and sample by collecting accurate numerical data from the population. Based on the results of the statistical test of this study of 273 participants who visited the Tourist Destination Lake Lut Tawar in Central Aceh, it was concluded that the quality of services and tourist attractions have no influence on the interests of visitors. But quality of service, touristic attractions, destination Image, facilities, each have a positive and significant impact on visitors' interests through satisfaction. The findings also suggest that the influence of these factors on visiting interests can be influenced by the demographics of respondents, with a majority of Generation Z and residing in the area of Lake Lut Tawar, Central Aceh.